Kolaborasi Guru dan Orang Tua dalam Meningkatkan Bacaan Al-Quran Santri: (Studi Kasus di Pondok Pesantren Assalam Kedungpari Mojowarno Jombang) - Abdul Rouf; Khoirul Huda; Khairul Muslim (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT This study aims to describe the collaboration between teachers and parents in improving students' Quran recitation and its impact on the quality of their Quran recitation at the Assalam Islamic Boarding School in Kedungpari, Mojowarno, Jombang. This study employed a descriptive qualitative approach, with data collection techniques including interviews, observation, and documentation. The data analysis technique employed the Milles and Huberman triangulation model, which includes three stages: data reduction, data presentation, and conclusion drawing or verification. The results indicate that the collaboration included active communication through WhatsApp groups, the use of a contact book, periodic parent-guardian meetings, and involvement in parenting activities. This collaboration significantly improved the quality of students' Quran recitation, both in terms of fluency, accuracy of pronunciation, and understanding of Tajweed. Supporting factors for the success of the collaboration included teacher and parent commitment and the use of digital media. Obstacles included time constraints, differences in parental backgrounds, and a lack of responsiveness from some parents. Keywords : Collaboration between Teachers and Parents, Al-Qur'an Reading by Students, Islamic Boarding Schools